2019
DOI: 10.1186/s12876-019-1109-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of perioperative outcome after hepatic resection for pediatric patients

Abstract: BackgroundHepatic resection is associated with significant risk of morbidity and mortality. Optimising the surgical techniques and perioperative management may improve in operative morbidity and mortality. However, perioperative variables involved in the improvement for postoperative outcomes in pediatric hepatectomy have not been defined.MethodsWe retrospectively reviewed 156 consecutive pediatric patients who underwent hepatectomy at our center (an academic tertiary care hospital) between 2006 and 2016. Base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
2
15
1
2
Order By: Relevance
“…To compare our results with existing evidence, an overview of studies reporting surgical outcomes of pediatric liver resection is given in Table 6 ( 2 4 , 10 , 12 , 13 , 16 19 , 40 – 44 ). Eleven single-center trials were found, with a median number of 27 reported cases in a median observation period of 15 year (1.8 cases per year on average).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To compare our results with existing evidence, an overview of studies reporting surgical outcomes of pediatric liver resection is given in Table 6 ( 2 4 , 10 , 12 , 13 , 16 19 , 40 – 44 ). Eleven single-center trials were found, with a median number of 27 reported cases in a median observation period of 15 year (1.8 cases per year on average).…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric patients are particularly susceptible to blood loss and low circulating blood volume. Strong negative effects on the patients' outcome have been reported previously (10,36,37). Adverse effects of blood transfusions, such as lung injury, transfusion-related acute circulatory overload and hemolytic transfusion reactions, occur more often in pediatric patients than in the adult population, with associated mortality rates as high as 15-30% (36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations